ALGORITHMIC DISCRIMINATION: A BLUEPRINT FOR A LEGAL ANALYSIS (EU and comparative law issues and challenges series (ECLIC), 2023)
The paper aims at providing an overview of the issues raised by algorithmic discrimination, and the key contributions proposed in the literature to address them. It is intended to be used as a starting point for those interested in approaching the topic for the first time or as a syllabus for the students taking the Erasmus+ Strategic Partnership MOOC “Time to Become Digital in Law”. First, the contribution will outline what algorithms are and what we consider algorithmic bias and what are its causes. Second, it will investigate the ethical and social implications of algorithmic bias. Then, the paper will focus on how existing laws and regulations can be applied to algorithmic discrimination. This contribution will focus in particular on the two branches of law that have been identified in the literature as the most relevant in this context: anti-discrimination law and data protection law. The work will outline their potentialities and limitations, presenting some proposals advanced in the literature to fill the new and emerging gaps of protection.